2018
DOI: 10.1007/s40093-018-0205-y
|View full text |Cite
|
Sign up to set email alerts
|

Organic manures: an efficient move towards maize grain biofortification

Abstract: Purpose In a novel approach, certain organic wastes byproducts of agro industries were assessed for their ability to support maize growth and Zn bioavailability in maize grain. Methods In a field experiment, maize (Zea mays) was supplemented with farm yard manure (FYM), press mud (PM), fisheries manure (FM), and slaughter house waste (SHW) in combination with Zn soil application (ZnS) and Zn foliar spray (ZnF) with recommended doses of N:P:K (140:100:60 kg ha −1 ), respectively. Besides assessing the maize gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
(6 reference statements)
2
10
0
Order By: Relevance
“…An increase in Zn concentration in maize grain is positively correlated with grain yield, test weight, cob diameter and cob length. These results corroborated with the findings of Sadiq Naveed et al (2018).…”
Section: Grain Qualitysupporting
confidence: 91%
See 1 more Smart Citation
“…An increase in Zn concentration in maize grain is positively correlated with grain yield, test weight, cob diameter and cob length. These results corroborated with the findings of Sadiq Naveed et al (2018).…”
Section: Grain Qualitysupporting
confidence: 91%
“…The increase in stover yield is due to adequate biomass production and better nutrient uptake. These results corroborated with the findings of Naveed et al (2018).…”
Section: Yieldsupporting
confidence: 91%
“…Despite a steady reduction in global dietary Zn deficiency in the last 20 years, more than 25% of the population in sub‐Saharan Africa (SSA) is still at risk of inadequate dietary Zn intake (Kumssa et al., 2015). While numerous experimental agronomic biofortification studies using Zn‐containing fertilizers have been conducted (e.g., Abdoli, Esfandiari, Mousavi, & Sadeghzadeh, 2014; Cakmak, 2008; Cakmak, Pfeiffer, & McClafferty, 2010a; Manzeke, Mtambanengwe, Nezomba, & Mapfumo, 2014; Manzeke et al., 2017; Zou et al., 2012), fewer studies have been conducted on maize ( Zea mays L.; e.g., Manzeke et al., 2014; Naveed et al., 2018; Zhang et al., 2013), the staple grain in most Southern African countries. Reducing Zn deficiencies in SSA is confounded by low fertilizer application (Jama & Pizarro, 2008; Kaizzi, Mohammed, & Nouri, 2017) and a scarcity of appropriate fertilizers (Mapfumo & Giller, 2001; Mtambanengwe & Mapfumo, 2005; Nezomba, Mtambanengwe, Rurinda, & Mapfumo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Remobilization of macronutrients and micronutrients to the grain or stover from the vegetative parts of maize are governed by the nutrient accumulation rates and DM . The study conducted by Naveed et al . showed that organic matter could be used to increase maize growth and Zn accumulations in the grain in a continuous manner.…”
Section: Discussionmentioning
confidence: 99%
“…Remobilization of macronutrients and micronutrients to the grain or stover from the vegetative parts of maize are governed by the nutrient accumulation rates and DM. 59 The study conducted by Naveed et al 60 showed that organic matter could be used to increase maize growth and Zn accumulations in the grain in a continuous manner. Achat et al 61 demonstrated that organic matter, specifically carbon, as well as the N ratio in regard to carbon and the P ratio in regard to K-Ca-Mg, is one of the factors influencing remobilization in plants.…”
Section: Effects Of Mg Application On the Distributions Of Mg In The mentioning
confidence: 99%